PROSES PEMBINAAN TERHADAP NARAPIDANA NARKOBA DI LEMBAGA PEMASYARAKATAN KELAS II A KEROBOKAN - Suendra, Dessy Lina Oktaviani; Setiabudhi, I Ketut Rai; Suardana, I Wayan (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 01, Januari 2013, 2013)
Number of drug crimes in Indonesia has made the public uneasy. Is not only a crime inthe trafficking of drugs but also drug abuse. Many means used by the government tocombat drug crimes, one way guidance systems in prisons. Guidance systems provideguidance to inmates in the form of personality and independence. It is intended that theprisoners who had been released from prison will be accepted back in the community.
Keywords: drug crime. prison, guidance system, community